Taking Europe To Its Extremes: Extremist Parties and Public Euroscepticism - Edwards, Erica; de Vries, Catherine (Sage Journals, 2009)
This article revisits the age-old debate about elite—mass linkages in the European Union (EU) by examining the way in which political contexts shape individual differentiation in Euroscepticism. We argue that the growing uncertainties about the future of European integration among national publics are increasingly politicized by Eurosceptical elites on both the extreme right and left of the political spectrum. To analyse the cueing effects of these extremist parties, we employ a two-level hierarchical linear model which combines individual-level and contextual data. We show that Eurosceptic cues are, indeed, found on both extremes, but for different reasons. Whereas right-wing extremist parties oppose European integration with the defence of `national sovereignty' and successfully mobilize national identity considerations against the EU, left-wing extremist parties resist further integration in Europe on the basis of the neoliberal character of the project and effectively cue voters against the EU on the basis of economic insecurity arguments.
Keywords: 59 Ciencia Política::5903 Ideologías políticas; ODS 10 - Reducción de las desigualdades